Human Obesity Induces Dysfunction and Early Senescence in Adipose Tissue-Derived Mesenchymal Stromal/Stem Cells - Conley, Sabena M.; Hickson, LaTonya J.; Kellogg, Todd A.; McKenzie, Travis; Heimbach, Julie K.; Taner, Timucin; Tang, Hui; Jordan, Kyra L.; Saadiq, Ishran M.; Woollard, John R.; Isik, Busra; Afarideh, Mohsen; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background Chronic inflammatory conditions like obesity may adversely impact the biological functions underlying the regenerative potential of mesenchymal stromal/stem cells (MSC). Obesity can impair MSC function by inducing cellular senescence, a growth-arrest program that transitions cells to a pro-inflammatory state. However, the effect of obesity on adipose tissue-derived MSC in human subjects remains unclear. We tested the hypothesis that obesity induces senescence and dysfunction in human MSC. Methods MSC were harvested from abdominal subcutaneous fat collected from obese and age-matched non-obese subjects (n = 40) during bariatric or kidney donation surgeries, respectively. MSC were characterized, their migration and proliferation assessed, and cellular senescence evaluated by gene expression of cell-cycle arrest and senescence-associated secretory phenotype markers. In vitro studies tested MSC effect on injured human umbilical vein endothelial cells (HUVEC) function. Results Mean age was 59 ± 8 years, 66% were females. Obese subjects had higher body-mass index (BMI) than non-obese. MSC from obese subjects exhibited lower proliferative capacities than non-obese-MSC, suggesting decreased function, whereas their migration remained unchanged. Senescent cell burden and phenotype, manifested as p16, p53, IL-6, and MCP-1 gene expression, were significantly upregulated in obese subjects’ MSC. BMI correlated directly with expression of p16, p21, and IL-6. Furthermore, co-incubation with non-obese, but not with obese-MSC, restored VEGF expression and tube formation that were blunted in injured HUVEC. Conclusion Human obesity triggers an early senescence program in adipose tissue-derived MSC. Thus, obesity-induced cellular injury may alter efficacy of this endogenous repair system and hamper the feasibility of autologous transplantation in obese individuals.